Evaluasi kepuasan pasien terhadap pelayanan resep rawat jalan di Rumah Sakit Anwar Medika - Khurin In Wahyuni; Rodhi Anshari; Novi Hartatik; Bella Fevi Aristia; Djelang Zainuddin Fickri (STIKes Surya Global Yogyakarta, 2021)
Pharmaceutical service is an effort that can be used to create social welfare. The community expects the best possible pharmacy services in the drug distribution process. The purpose of this study is to determine the level of patient satisfaction on the quality of pharmaceutical services at the outpatient installation of Anwar Medika Hospital. The study was observational with survey method. Primary data were collected on 147 respondents. Respondents conducted by using purposive sampling. Respondents were patients who got pharmaceutical care in outpatient installation of Anwar Medika hospital. The research instrument used a likert scale answer type questionnaire. Data analysis was conducted using the community satisfaction index and Cartesian diagram. The results of the analysis using the community satisfaction index based on five dimensions showed that the reliability dimension has an average of 73.75, responsiveness 73.00, assurance 70.75, empathy 70.75 and tangible 73.75. Overall, respondent rate pharmaceutical services in outpatient installation of Anwar Medika hospital was satisfactory. The results of the Cartesian diagram analysis showed that there were 2 questions that were in I quadrant, namely related to the speed of pharmacy services in serving prescriptions (responsiveness dimension) and the number of seats sitting in the waiting room was sufficient (tangible dimension). This research can be concluded that the patients are satisfied with the pharmaceutical services at the Outpatient Installation of Anwar Medika Hospital. The assessment elements on the speed of prescription services and the number of waiting chairs need to be evaluated and improved to improve the quality of service and meet satisfaction on the dimensions of responsiveness and tangibles.